Contacts with, and attitudes toward, the mentally ill in the New Zealand police : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Rowe, Tracey Marie (Massey University, 2001)
Deinstitutionalisation and changes to the Mental health Act (1992) relating to committal and treatment for those with a mental illness has resulted in increased numbers of people with a mental illness living in the community. Internationally these changes in the care of mentally ill people have resulted in increased contacts between the police and the mentally ill. The present study investigated the amount, and nature of, contacts between the New Zealand police and the mentally ill and the attitudes of the police toward mentally ill persons using Cohen and Struenings Opinions about Mental Health (OMI) scale. Self-administered questionnaires were distributed to all police stations within region three of the New Zealand police districts and a total of 261 sworn police participated. The results show that New Zealand police, like their international colleagues, experience regular contacts with the mentally ill that are time consuming, stressful and largely non-criminal in nature. While the police expressed a dislike to attending call outs involving the mentally ill, their attitudes as measured by the OMI were overall positive and accepting of mentally ill people. The participants expressed a desire for additional training and education to better prepare themselves to deal with the mentally ill.
Irregular pagination: pg 56 missing
Keywords: New Zealand; Police -- Attitudes; Mentally ill -- Services for